2007
DOI: 10.1002/cpp.532
|View full text |Cite
|
Sign up to set email alerts
|

Relations between different types of jealousy and self and partner perceptions of relationship quality

Abstract: The present paper examines the relationships between relationship quality and three different types of jealousy, including both partners' levels of jealousy and perceptions of relationship quality. It was expected that jealousy in response to a direct threat to the relationship-that is, reactive jealousy-would be positively related to relationship quality, whereas forms of jealousy that may also be triggered in the absence of such a threat would be negatively related to relationship quality. Three studies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
85
2
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 43 publications
4
85
2
3
Order By: Relevance
“…High scores of jealousy, especially cognitive jealousy (elphinston & Noller, 2011) indicated minor adjustment, satisfaction and perception of quality in the relationship (Barelds & Barelds-Dijkstra, 2007;DiBello et al, 2015;Khanchandani & Durham, 2009). Mathes (1986) made two applications of the interpersonal Jealousy scale to the same sample of people with a period of seven years, and indicated that the effects of jealousy could be positive, in that couples were married and their love continued.…”
Section: Interpersonal Variables: Relationshipmentioning
confidence: 99%
“…High scores of jealousy, especially cognitive jealousy (elphinston & Noller, 2011) indicated minor adjustment, satisfaction and perception of quality in the relationship (Barelds & Barelds-Dijkstra, 2007;DiBello et al, 2015;Khanchandani & Durham, 2009). Mathes (1986) made two applications of the interpersonal Jealousy scale to the same sample of people with a period of seven years, and indicated that the effects of jealousy could be positive, in that couples were married and their love continued.…”
Section: Interpersonal Variables: Relationshipmentioning
confidence: 99%
“…Overall, considerable attention has been given to the associations between dimensions of romantic jealousy and relationship outcomes such as relational quality, uncertainty, and satisfaction (e.g., Afifi & Reichert, 1996;Barelds & Barelds-Dijkstra, 2007;. However, researchers have yet to form any robust conclusions regarding the links between jealous thoughts and behaviors and relationship evaluations, and the causal nature of these associations remains unclear.…”
Section: Dimensions Of Romantic Jealousy and Negative Relationship Oumentioning
confidence: 99%
“…However, other research has yielded more mixed findings. Specifically, Barelds and Barelds-Dijkstra (2007) studied three types of romantic jealousy (as outlined by Bringle, 1991;Buunk, 1997)-reactive, anxious, and possessive (or preventative). Reactive jealousy refers to the extent to which individuals feel jealousyrelated emotions in response to an actual partner infidelity, while anxious jealousy is defined as an active cognitive process related to worries about partner behavior in the face of possible partner infidelity; possessive or preventative jealousy involves behaviors designed to prevent partner contact with a third party (again, in response to possible partner infidelity).…”
Section: Dimensions Of Romantic Jealousy and Negative Relationship Oumentioning
confidence: 99%
See 2 more Smart Citations